Relationship Between Maternal Education and Knowledge on Coverage of Exclusive Breastfeeding in Ten Stunting Locus Villages in Pandeglang District, Banten - Sri Wuryanti; Himmi Marsiati (Indonesian Journal of Medical Sciences and Public Health, 2021)
Introduction: Until now, the practice of exclusive breastfeeding is still far from the national target. The success of exclusive breastfeeding is determined by many factors, including the mother’s education, knowledge, and awareness about the importance of breastfeeding for child growth. This study aims to determine the relationship between the mother’s level of education and knowledge on exclusive breastfeeding in ten stunting locus villages located in Pandeglang Regency, Banten, Indonesia. Methods: This study uses a cross-sectional design with data collection methods through interviews and direct observation. The population consists of mothers who have children under 2 years of age. The study was conducted for 6 months from November 2019. The variables studied included the mother’s age, occupation, number of children, education, and knowledge of exclusive breastfeeding. Result: As many as 99.6% of respondents have a good level of knowledge about exclusive breastfeeding. The level of education is low at 44.6%, medium at 50.9%, and high at 4.4%. The results showed there was no significant relationship between the mother’s last education and exclusive breastfeeding (p = 0.860) and there was no significant relationship between the mother's level of knowledge and exclusive breastfeeding (p = 0.558). Conclusion: No significant relationship was observed between the mother’s education and knowledge on exclusive breastfeeding in ten stunting locus villages located in Pandeglang Regency, Banten.